AI-Generated Misinformation: A Literature Review - Fatimah, Rafharum; Mumtaz, Auziah; Fahrezi, Fauzan Muhammad; Zakaria, Diky (Indonesian Journal of Artificial Intelligence and Data Mining, 2024)
The expansion of artificial intelligence (AI) technologies has signaled an entirely new era in which the creation and sharing of information, both correct and misleading, are becoming increasingly automated. This research of the literature explores the landscape of AI-generated misinformation, including its various manifestations, underlying technology, societal impact, and detection tools. This paper reviews articles from the Google Scholar database related to AI-Generated Misinformation focusing on the following research questions: the types, content distribution, detector variations, differences among the various tools, and strategies for developing AI-based tools. The result is to provide an absolute comprehension of this topic, underlining the importance of interdisciplinary collaboration, robust detection methods, and media literacy with the intention to solve the ethical and societal issues it poses in the age of digital technology.